Dampak Green Strategy dan Green Innovation terhadap Performance Sustainability dengan Dimoderasi oleh Digital Transformation pada Perusahaan Manufaktur - Erna Kurniawati; Willy Arafah (Yayasan Literasi Sains Indonesia, 2026)
This qualitative research aims to analyze the role of green strategy and green innovation in improving sustainability performance, and to reveal how digital transformation affects this relationship in the context of modern business competition so that it can be a guide for managers in making strategic decisions to determine investments and their types. Data collection techniques were carried out systematically through qualitative techniques which included literature studies and documentation. The existing literature has not adequately integrated sustainability strategies with digital transformation as a determinant of green strategy effectiveness. The novelty of this research is that most studies only examine the direct or mediating effects of digital transformation, whereas this study examines its moderating effects. Based on the research results, all 4 hypotheses can be accepted, namely green strategy has a positive effect on green innovation, green innovation has a positive effect on sustainability performance, green strategy has a positive effect on sustainability performance, green strategy has a positive effect on sustainability performance and green strategy has a positive effect on sustainability performance with the moderating effect of digital transformation. The implementation of the right green strategy will facilitate the implementation of green innovation and contribute to sustainable development goals as well as promote environmentally responsible businesses in the global market by adopting digital transformation to address environmental issues, respond to consumer demands, save costs and comply with government regulations.